The influence of service quality, price, and payment procedures on Telkomsel prepaid card customer satisfaction - Briliani, Indri; Suhardi, Suhardi (Economic: Journal Economic and Business, 2026)
This study analyzes the influence of signal quality, package price, and ease of administrative procedures on customer satisfaction among Telkomsel prepaid card users, with customer trust as a mediating variable. A quantitative approach was used through an online survey involving 209 active Telkomsel customers who had experience using data packages, assessing network quality, and carrying out administrative processes such as SIM card replacement. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate the measurement and structural models. The results show that signal quality has the strongest influence on customer trust and also has a significant direct impact on customer satisfaction. Package price has a positive effect on customer trust and satisfaction, although its contribution is lower than that of signal quality. Ease of card replacement is proven to have a significant effect on customer trust, but does not have a direct effect on customer satisfaction. Customer trust is proven to play an important role as a mediating variable that strengthens the relationship between the three independent variables and customer satisfaction. These findings emphasize the importance of reliable network quality, fair pricing structures, and efficient administrative services in increasing customer trust and satisfaction in the competitive telecommunications industry.